Love your parents Quran stories for little hearts - Khan, S (India, Good words kidz, 2011)
This book highlights the teachings of the Qur'an and Hadith regarding the treatment of parents. It explains that loving and obeying one's parents is a fundamental moral principle in Islam. Through simple text and vivid illustrations, children learn that pleasing their parents pleases Allah. The book encourages children to pray for their parents, assist them, and avoid actions that may displease them.